Hierarchical data grid resource allocation based on quotient space theory - Chun-zhong XIA; Shun-lin SONG (Tongxin xuebao)
In order to solve the problems of falling into local optimum value and converging too slowly when allocating resources in hierarchical data grid using traditional algorithms,the granular computing was introduced and a quotient space theory based hierarchical data grid resource allocation (QSHDGRA) algorithm was proposed.Firstly,the charac-teristics of hierarchical data grid were analyzed.Secondly,a reconciling model of minimum average waiting time and maximum network and node resource utilization was defined,and then the QSHDGRA algorithm was designed.The al-gorithm can allocate resources from coarse granularities to fine ones,so it can guarantee the QoS of different businesses and make global optimal resource allocation.Simulation results show that QSHDGRA can improve overall system throughput with faster convergence speed and linear scalability.